2001
DOI: 10.1046/j.1444-2906.2001.00243.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dietary fat and carbohydrate levels on growth and body composition of rainbow trout Oncorhynchus mykiss under self-feeding conditions

Abstract: SUMMARY: An 8‐week feeding experiment was conducted to examine the influence of fat and carbohydrate levels in a 40% protein level diet on growth and body composition of rainbow trout Oncorhynchus mykiss under self‐feeding conditions. Five fish meal‐based diets were prepared to include gelatinized potato starch at four levels (9, 18, 27, and 36%) and dextrin (34%). Dietary fat levels were isoenergetically reduced from 18 to 7% by the digestible carbohydrates. Each diet was fed to four replicate groups (28 g/fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 28 publications
1
28
0
1
Order By: Relevance
“…Moreover, fish show a reduced ability to digest carbohydrates with high molecular complexity or not pretreated (Peres and Oliva-Teles, 2002;Venou et al, 2003;Enes et al, 2006). Additionally, in general, starch or more simple carbohydrates such as dextrin or maltose (except glucose) digestibility appears to decrease with increasing dietary levels (Hutchins et al, 1998;Skalli, 2001;Yamamoto et al, 2001;Enes et al, 2006). The appropriate dietary inclusion level of digestible carbohydrates has been established between a recommended 20% maximum for carnivorous species, and 40% for hot water omnivorous species (Wilson, 1994;Stone, 2003), although the observed responses for different types and levels of carbohydrates are varied (McMeniman, 2003;Mohapatra et al, 2003;Stone et al, 2003;Enes et al, 2011).…”
Section: Introductionmentioning
confidence: 95%
“…Moreover, fish show a reduced ability to digest carbohydrates with high molecular complexity or not pretreated (Peres and Oliva-Teles, 2002;Venou et al, 2003;Enes et al, 2006). Additionally, in general, starch or more simple carbohydrates such as dextrin or maltose (except glucose) digestibility appears to decrease with increasing dietary levels (Hutchins et al, 1998;Skalli, 2001;Yamamoto et al, 2001;Enes et al, 2006). The appropriate dietary inclusion level of digestible carbohydrates has been established between a recommended 20% maximum for carnivorous species, and 40% for hot water omnivorous species (Wilson, 1994;Stone, 2003), although the observed responses for different types and levels of carbohydrates are varied (McMeniman, 2003;Mohapatra et al, 2003;Stone et al, 2003;Enes et al, 2011).…”
Section: Introductionmentioning
confidence: 95%
“…A suitable feeding regime with optimal feeding frequency and temperature not only enhances growth and feeding efficiency of fish, but also minimizes size variations, feed waste, production cost, and disease occurrence [34][35][36][37]. Water temperature and feeding frequency are two important components affecting growth, which have been studied in several fish species such as Channel catfish [38], European seabass [39], rainbow trout [40,41], Tiger Puffer [42], tilapia [24], pikeperch [43], and Asian seabass [44]. Temperature affects food consumption, digestion rate, and growth rate through variations in metabolism [15,45], use of nutrients and energy [18,46], and digestive enzyme activities [17,[47][48][49].…”
Section: Optimal Temperature and Feeding Frequencymentioning
confidence: 99%
“…Because in both these diets 350 Low and 350 High the dietary protein level was much below the requirement of the fish, fish enhanced its feed intake to compensate for this deficiency. Also, diet 450 High contained highly imbalanced levels of 450 g/kg protein and 4.54 kcal/g energy; hence, the reduction in feed intake in fish fed diet 450 High may be due to higher levels of both protein and energy in this diet, and it has been predicted that consumption of a diet is inversely related to its protein and energy content (Yamamoto et al 2001). El‐Dahhar and Lovell (1995) have also reported that excess energy in tilapia diets may have led to a reduced feed consumption.…”
Section: Discussionmentioning
confidence: 99%